Employee motivational factors: a comparison between Malaysia and Sultanate of Oman - Abdullah, Muhammad Madi; Islam, Rafikul (Inderscience, UK, 2012)
Industrial psychologists have continuously devised theories and executives and managers have tirelessly formulated various programmes related to employee motivation. A set of committed, motivated employees is an asset for any organisation – public or private. A well-known fact is that an organisation can emulate almost anything of another organisation except its human resources. How to motivate employees? Can one particular factor motivate everybody equally? Is there any cultural influence on motivating factors? Extensive investigations have been made to address these fundamental questions in the last few decades. This research, which is a sequel to the previous researches, basically aims at identifying the salient motivating factors for Malaysian as well as Omani employees. A detailed comparison has been made on the findings of the motivating factors with regard to the two countries. Finally, managerial implications are highlighted for both the countries.